THE EFFECTS OF SHARIAH GOVERNANCE ON TAKAFUL PERFORMANCE OF TAKAFUL OPERATORS IN MALAYSIA - Nurul Nazlia Jamil; Ainulashikin Marzuki (Journal of Islamic, Social, Economics and Development, 2023)
This study investigates the relationship between the Shariah Governance and he financial performance of Takaful operators in Malaysia. There are a lot of researches focused on determinants factors that affecting the financial performance of banks rather than insurance companies especially in Malaysia. Thus, this study is very important and beneficial to regulators, investors and customers. By understanding determinants contributing to the financial performance, the regulators could play a vital role in helping Takaful operators to increase their market share. Hence, the objective of the paper is to investigate the relationship between shariah governance and financial performance of Takaful operators in Malaysia. Data were gathered using secondary data collection method from annual report for each of Takaful operators and Bank Negara Malaysia from year 2018 until 2022. The data consist of profitability, Shariah Committee, Shariah Risk Management and Shariah Review for 5 registered Takaful operators in Malaysia namely; Syarikat Takaful Malaysia Berhad, Takaful Ikhlas Sdn Bhd, Prudential BSN Malaysia Berhad, Sun Life Malaysia Takaful Berhad (CIMB Aviva Takaful Berhad) and Hong Leong MSIG Takaful Berhad. Data were analysed using multiple regression analysis. From the analysis, Shariah Committee was found significantly positive effect towards financial performance. In contrast, Shariah Risk Management and Shariah Review were found significantly negative effect related to the financial performance. Thus, this study is very important and beneficial to regulators, investors and customers. As recommendation, Takaful operators should improve their effectiveness of the Shariah Governance through expanding the size of Shariah Committee, hiring more experts in Islamic and risk management in designing effective policy for the Takaful operators. Regulators could use this study to formulate of suitable and useful ways to efficiently supervise the operations of Takaful insurance.